Teori Pendidikan Keluarga dan Tanggung Jawab Orang Tua dalam Pendidikan Anak Usia Dini - Jailani, M. Syahran (Nadwa, 2014)
This paper describes the responsibilities of parents in early childhood education. From the review of the literature it is known that the family environment be-comes a major place of a child to education. Father and mother in the family becomes the first educators in the process of development of a child's life. Par-ents do not just build a relationship and do various family for reproductive pur-poses, continue descent, and establish affection. The main task of the family is to create buildings and atmosphere of family education process so that the next generation of intelligent and noble generation as a solid footing in the tread life and the journey of human children. The fact is supported by the findings of the theories that support the importance of family education as the first basic educa-tion of children.Â AbstrakMakalah ini menjelaskan tanggung jawab orang tua dalam pendidikan anak usia dini. Dari kajian literatur diketahui bahwa lingkungan keluarga menjadi tempat yang utama seorang anak memperoleh pendidikan. Ayah dan ibu dalam keluarga menjadi pendidik pertama dalam proses perkembangan kehidupan anak. Orang tua tidak sekedar membangun silaturahmi dan melakukan berbagai tujuan berkeluarga untuk reproduksi, meneruskan keturunan, dan menjalin kasih sayang. Tugas utama keluarga adalah menciptakan bangunan dan suasana proses pendidikan keluarga sehingga melahirkan generasi yang cerdas dan berakhlak mulia sebagai pijakan yang kokoh dalam menapaki kehidupan dan perjalanan anak manusia. Kenyataan tersebut ditopang temuan teori-teori yang mendukung pentingnya pendidikan keluarga sebagai dasar pertama pendidikan anak-anak.